The dark side of stress tests: Negative effects of information disclosure - Goncharenko, Roman; Hledik, Juraj; Pinto, Roberto (Journal of Financial Stability, 2018)
This paper studies the effect of information disclosure on banks’ portfolio risk. We cast a simple banking system into a general equilibrium model with trading frictions. We find that the information disclosure lowers the expected risk-adjusted profits for a non-negligible fraction of banks. The magnitude of this effect depends on the structure of the banking system and, alarmingly, it is more pronounced for systemically important institutions. We connect these theoretical findings to the stress test procedure, where bank information is disclosed by the regulator. The 2011 and 2014 stress tests are used in an empirical study to further support our theoretical results.